Understanding heterogeneous spatial production externalities as a missing link between land-use planning and urban economic futures. Issue 1 (2nd January 2021) - Pan, Haozhi; Yang, Tianren; Jin, Ying; Dall'Erba, Sandy; Hewings, Geoffrey
ABSTRACT: Land-use planning influences economic performance as it can intervene with location-specific and heterogeneous production externalities. This paper examines the impacts of heterogeneous externalities on local employment growth using a panel model framework with block-level land-use data inventory for Chicago. Cross-industry spillovers provide positive impacts on growth, but the mechanisms behind them differ across sectors and spatial scales. Improved understanding of heterogeneity in agglomeration economies can better support plan-making and urban economic performance. The results show significant and positive influence of cross-industry spillovers, a missing consideration in existing planning processes.